Let
f
(
x
)
=
x
2
−
5
. If
f
(
6
)
−
f
(
4
)
=
f
(
y
)
, what is
∣
y
∣
?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
P u t x = 6 a n d x = 4 i n f ( x ) = x 2 − 5 : 3 6 − 5 − 1 6 + 4 = f ( y ) 2 0 = y 2 − 5 2 5 = y 2 y = ± 5 ∣ y ∣ = 5
Cheers!!!:):)
Why did you write the answer in the question ?
I did it the same way
Problem Loading...
Note Loading...
Set Loading...
The answer is in the picture. That's what I did